2020
DOI: 10.1111/ced.14342
|View full text |Cite
|
Sign up to set email alerts
|

Cutis laxa‐like calcinosis cutis secondary to asfotase alfa in juvenile‐onset hypophosphatasia

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(9 reference statements)
0
3
0
Order By: Relevance
“… 8 , 9 Importantly, there are 2 documented cases of calcinosis cutis after AA therapy. Charalambides et al 10 reported a case of severe injection site reaction to subcutaneous injections of AA in a patient with juvenile-onset HPP receiving 60 mg AA for 6 days per week for 6 months alternating in the abdomen and thigh. 10 Skin biopsies at these injection sites showed calcium deposition in the dermis, subcutis, vessel walls, and sweat ducts with a multinucleate giant cell response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 , 9 Importantly, there are 2 documented cases of calcinosis cutis after AA therapy. Charalambides et al 10 reported a case of severe injection site reaction to subcutaneous injections of AA in a patient with juvenile-onset HPP receiving 60 mg AA for 6 days per week for 6 months alternating in the abdomen and thigh. 10 Skin biopsies at these injection sites showed calcium deposition in the dermis, subcutis, vessel walls, and sweat ducts with a multinucleate giant cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Charalambides et al 10 reported a case of severe injection site reaction to subcutaneous injections of AA in a patient with juvenile-onset HPP receiving 60 mg AA for 6 days per week for 6 months alternating in the abdomen and thigh. 10 Skin biopsies at these injection sites showed calcium deposition in the dermis, subcutis, vessel walls, and sweat ducts with a multinucleate giant cell response. The pathophysiology of this reaction is due to degradation of PPi by synthetic ALP found in AA; degraded PPi produces higher levels of inorganic phosphate, which promote calcification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation